CHANGES IN FISHING EFFICIENCY OF THE POLE-AND-LINE SKIPJACK TUNA FLEET BASED AT SORONG IRIAN JAYA, INDONESIA - Nicholas J.F. Rawlinson; Budi Iskandar Prisantoso; David A. Milton; Bachtiar Gafa (Research Center for Fisheries, 1998)
Data from the fishing operations of the pole-and-line fishing fleet based in Sorong, IrianJava, eastern Indonesia are examined to assess the status of the fishery in that region.